2014
DOI: 10.1016/j.ijgo.2014.03.038
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between female genital cutting and women's autonomy in Eritrea

Abstract: Interventions addressing women's autonomy, specifically attitudes toward gender norms and increasing women's involvement in household decisions that carry a greater responsibility, may be a useful approach to reduce the support for and practice of FGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Overall, eight articles showed a low risk of bias,26 35–41 20 articles had a high risk of bias10 21 24 25 27 30–32 34 42–52 and 26 articles demonstrated an unclear risk of bias 17–20 22 23 28 29 33 53–69…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, eight articles showed a low risk of bias,26 35–41 20 articles had a high risk of bias10 21 24 25 27 30–32 34 42–52 and 26 articles demonstrated an unclear risk of bias 17–20 22 23 28 29 33 53–69…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies assessed the association between being Muslim and FGM/C status among women (n=15) and girls (n=9) 18 19 22 23 27 28 30 31 35 36 39–41 46 51 54 57–59 61–63 66 68. Overall, 15 studies found a significant positive association between being Muslim and FGM/C status18 19 22 27 28 30 31 35 36 39 40 57–59 61 and nine found no significant relationship 23 41 46 51 54 62 63 66 68.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We build on that individualistic orientation by also considering how household dynamics and community norms influence women's decisions to have their daughters cut. Women's abilities to make major decisions within their households can be one manifestation of their agency because households are sites where gender roles and decision making strategies play out daily (Besera & Roess, ; Kabeer, ; Upadhyay et al, ). Decision making within households can take several forms: Women may defer to their partners on major household decisions, they may discuss important issues with their partners and come to decisions jointly, or they may make major decisions on their own without consulting their partners.…”
Section: Hypothesesmentioning
confidence: 99%
“…We examine the association between women's status and medicalisation of FGC using the two most recent waves of the Egyptian Demographic Health Survey. A comprehensive conceptualisation of women's social status, broadly defined as women's ability to have control over the circumstances of their lives (Besera and Roess, 2014), is incorporated by taking women's status both within and outside the household into account.…”
Section: Introductionmentioning
confidence: 99%